Pedagogy of love on the way to the inclusion of people with Down Syndrome through the provision of sports education - Laura Arevalo Aguilar, Laura Arevalo Aguilar (Southern perspective / Perspectiva austral, 2024)
The article addresses the use of love pedagogy as an effective approach to promote the inclusion of people with Down syndrome through sports education. It highlights how this approach, centered on love, empathy and mutual respect, can create an environment conducive to the active participation and comprehensive development of individuals with Down syndrome in sporting activities. Specific pedagogical strategies, such as adapting activities and individualized attention, are discussed to ensure an inclusive and enriching experience for all participants. The fundamental role of sports education is highlighted as a tool to promote social inclusion, empowerment and improving the quality of life of people with Down syndrome